Medium‐Scale Traveling Ionospheric Disturbances Observed by Detrended Total Electron Content Maps Over Brazil. Issue 3 (14th March 2018) - Figueiredo, C. A. O. B.; Takahashi, H.; Wrasse, C. M.; Otsuka, Y.; Shiokawa, K.; Barros, D.
Abstract: A ground‐based network of Global Navigation Satellite Systems receivers has been used to monitor medium‐scale traveling ionospheric disturbances (MSTIDs). MSTIDs were studied using total electron content perturbation maps and keograms over south‐southeast of Brazil during the period from December 2012 to February 2016. In total, 826 MSTIDs were observed mainly in daytime, thus presenting median values of horizontal wavelength, period, and horizontal phase velocity of 452 ± 107 km, 24 ± 4 min. and 323 ± 81 m/s, respectively. The direction of propagation varies on the season: during the winter (June–August), the waves preferentially propagated to north‐northeast, while in the other seasons the waves propagated to other directions. The anisotropy observed in the MSTID propagation direction could be associated with the region of the gravity wave generation that takes place in the troposphere. We also found that the MSTIDs were observed most frequently during the daytime, between 11 and 15 local time in winter and near to dusk solar terminator (17–19 local time) in the other seasons. Furthermore, the occurrence of MSTIDs was higher in winter. We suggest that atmospheric gravity waves in the thermosphere, mesosphere, and troposphere could play an important role in generating the MSTIDs and the propagation direction may depend on location of the wave sources. Key Points: The paper presents the statistical study of MSTIDs in equatorial latitudes over south‐southeast of Brazil The propagation direction of MSTIDs changes according to the seasons The MSTIDs can be originated by gravity waves that propagate from the lower atmosphere